Trabalho e educação na capacitação artesanal: caso Boliviano - Chavez Ballon, Anna Elizabeth (1993)
The educational conception that the craftsmen have in general, is winder than the simple practice of formal education. It’s clear for the craftsmen, than the relationship among people and groups, are educational facts than guide towards reaching various objectives such as labor and production. The craftsmen instruction is an expression of the education that has several objectives, prosses and dimentions that must be worked inside of the craftsmen group in accordance to its needs. The instructions must be and instrument that supports all the progress and development of craftsmen and their organization. As a consequence the educational component called instruction, will be an important element of support to catch one of the tasks related to the craftsmen job. The dimention of the craftsmen instruction will have to reach a human technic integrity, in the education; these dimentions can not be limited by operative technics, financial, logistic, and administrative topics, on the contrary it is necessary to get some consciousness and participative practice, reaching with this social and political dimentions inside the reaching with this social and political dimentions inside the craftsmen practice. These dimention have as a previous condition the generalization of the basic school in the perspective of their interests, needs and goals.